The transition from exhaustible to renewable resources: Investigating the dynamic effect of natural resources and monetary liquidity on consumption of renewable energy - Lunku, Hassan Swedy; Tebo, Felix Exavery; Masanyiwa, Costantine Felix (Universitas Ahmad Dahlan, 2026)
The global shift towards renewable energy is central to climate change mitigation, yet adoption remains uneven, particularly in resource-rich economies where financial liquidity constraints and fossil fuel dependence persist. This study advances the literature by providing a novel integrated analysis of how financial liquidity, digitalisation, and institutional quality jointly shape renewable energy adoption in both resource-abundant and resource-scarce economies. Using a dynamic panel data model, the research examines interactions among financial depth, digital advancements, and institutional quality in 124 economies, showing that good governance and financial policies can convert resource wealth into renewable energy drivers. Results indicate that broad money significantly predicts renewable energy usage, dependent on regulatory frameworks that encourage green investments. The traditional resource curse hypothesis is challenged, demonstrating that strong regulations can utilise natural wealth for sustainable energy transitions. This study contributes new evidence to the renewable energy–finance nexus and suggests that policymakers should focus on financial instruments supporting green initiatives, enhancing digital infrastructure, and enforcing solid governance. Resource-rich countries can maximise their energy potential by aligning monetary policies with sustainability objectives, fostering a cleaner and more sustainable future.